Divine blessings - Norhafsah Hamid (Iman Publication, 2020)
Sarah and Jonah are blissfully content after their marriage. Their friends - Jaws, Linda, and Mat Bond are all leading happy lives despite adjusting to the commitments of adulthood. Through ups and downs, their friendship remained strong. But in life, love and happiness require hard work and sacrifice. For some, life will come to a beautiful full circle - proving that eternal happiness is foreveryone, even if one was once, so far away from God.